The outsiders [videorecording (DVD)] - Dillon, Matt; Cruise, Tom, 1962-; Estevez, Emilio, 1962-; Howell, C. Thomas, 1966-; Lane, Diane; Swayze, Patrick; Lowe, Rob; Macchio, Ralph, 1961-; Hinton, S. E. (Warner Bros. Entertainment : Distributed by Warner Home Video, 2008)
Francis Ford Coppola's stylized teen melodrama is based on the popular novel by S. E. Hinton. In 1960s Tulsa, the "right" and "wrong" sides of the tracks are represented by rival gangs, the upscale Socs and the underprivileged Greasers. Darrel Curtis (Patrick Swayze) is doing his best to raise his two younger brothers, Sodapop (Rob Lowe in his first film role) and Ponyboy (C. Thomas Howell). Sensitive Ponyboy is a budding writer in love with Cherry (Diane Lane), the unobtainable beauty from the enemy gang. When Ponyboy's buddy, troubled Johnny Cade (Ralph Macchio), kills one of the Socs in self-defense, their friend Dallas (Matt Dillon) helps the two youths hide out in an abandoned country church. There they live as exiles from a society that doesn't want them. But not all is lost, when Ponyboy, Johnny, and Dallas save some children caught in a fire they become unlikely heroes. -- from http://www.moviemars.com (Sep. 20, 2011).